Дослідження методів побудови рекомендаційної системи для реалізації товарів в інтернет-просторі - Новік, В. Є. (ХНУРЕ, 2023)
The purpose of this work is to research methods that will help build a recommender system for selling goods in the Internet space. In the course of the study, it was decided to use machine learning capabilities to help the customer choose products, namely to provide recommendations for products that would best meet the customer's needs. Methods and algorithms were explored for designing and building a system that could solve the customer's problem of purchasing the most appropriate product for their needs and budget.